Sodium-Glucose Cotransporter 2 Inhibitors Potentially Prevent Atrial Fibrillation by Ameliorating Ion Handling and Mitochondrial Dysfunction - Peng, Xiaodong; Li, Linling; Zhang, Mengxia; Zhao, Qianqian; Wu, Kui; Bai, Rong; Ruan, Yanfei; Liu, Nian (Frontiers in Physiology, 2020)
Sodium-glucose cotransporter 2 inhibitors (SGLT2i) are a novel class of glucose-lowering agents that significantly improve the prognosis of patients with type 2 diabetes (T2D) and heart failure. SGLT2i has recently been implicated in the treatment of atrial fibrillation (AF) with clinical data demonstrating that these agents decrease the incidence of AF events in patients with T2D. Fundamental findings have suggested that SGLT2i may alleviate atrial electrical and structural remodeling. The underlying mechanisms of SGLT2i are likely associated with balancing the sodium and calcium handling disorders and mitigating the mitochondrial dysfunction in atrial myocytes. This review illustrates the advances in understanding the underlying mechanisms of SGLT2i as an evolving treatment modality for AF.